Vibrational-rotational analysis of the Hulthén potencial using hydrogenic eigenfunction bases - Aguilera-Navarro, V. C. [UNESP]; Ley-Koo, E. [UNESP]; Mateos-Cortés, S. (My University, 1998)
Hulthén's potential admits analytical solutions for its energy eigenvalues and eigenfunctions corresponding to zero orbital angular momentum states, but its non zero angular momentum states are not equally known. This work presents a vibrational-rotational analy sis of Hulthén's potential using hydrogenic eigenfunction bases, which may be of interest and useful to students of quantum mechanics at different stages.
Keywords: Hulthén's potential; Quantum mechanics; Variational solutions